Prediction of mould growth rate within building envelopes: development and validation of an improved model. (January 2023) - Zeng, Lingjie; Chen, Yuqing; Ma, Mingyao; Du, Bowen; Gao, Jun; Cao, Guoqing; Li, Jingguang
Mould growth is a common problem in building envelopes. This issue is usually caused by poor design and construction of walls and results from the difference between indoor and outdoor climatic conditions. Mould spores produced by mouldy walls may diffuse into the air, thereby affecting indoor air quality and threatening occupant health. Therefore, it is important to predict the risk of mould growth in building envelopes under various conditions. This study selected three buildings from a traditional community in Shanghai, China. First, the mould species in these building envelopes were identified. Based on the identification results, the growth rate of the corresponding genera was extracted from the literature to establish an isoline model that describes mould growth on the agar surface. In addition, the mould growth rate between and outside the isoline areas was predicted by modifying the Sautour model to relevant air temperature and humidity conditions. According to the results of the proposed model, the critical temperature and humidity that allow the growth of representative moulds from the buildings selected for this study can be expressed as φ =0.002633·cosh[0.10083·( θ -30)]+0.7153. The accuracy of the above model was verified experimentally, and the maximum relative error of the growth rate was within 25%.